Digital literacy in the university setting: A literature review of empirical studies between 2010 and 2021 - Gutiérrez-Ángel, Nieves; Sánchez-García, Jesús-Nicasio; Mercader-Rubio, Isabel; García-Martín, Judit; Brito-Costa, Sonia (Frontiers in Psychology, 2022)
The impact of digital devices and the Internet in today's society has generated various changes at social, political and economic levels, the repercussion of which is a great challenge in today's society, characterized by being a changing and globalized society, which demands the development of new skills and a new learning model in relation to information and communication technologies. The university must respond to these social demands in the training of its future professionals. The aim of this paper is to analyze the empirical evidence provided by international studies in the last seven years, related to the digital literacy of university students, including those pursuing degrees related to the field of education. The results found highlight the fact that the digital literacy that is offered from the university to university students who are pursuing some type of degree or postgraduate degree related to education, in addition to treating digital literacy as a central theme, they also do in terms of perceived and developed self-efficacy: competencies related to digital writing and reading, the use of databases, the digital design of content and materials, and the skills to edit, publish or share them on the web, or applications aimed at treating the digital literacy as emerging pedagogies and educational innovation. As well as, secondly, we find studies related to digital competence and the use and use of the Internet, social networks, web 2.0, or the treatment of digital risks and their relationship with digital literacy. And, thirdly, we find works that, in addition to focusing on digital literacy, also focus on different psychological constructs such as motivation, commitment, attitudes or satisfaction.